Potential Association Between Asthma, Helicobacter pylori Infection, and Gastric Cancer - Wu, Fengxia; Chen, Cai; Peng, Fulai (Frontiers in Oncology, 2021)
Backgroud: The prevalence of hylicobacter pylori infection (HPI) was still high around the world, which induced gastric diseases, such as gastric cancer and gastritis. The epidemiological investigation showed that there was an association between HP infection and asthma. Purpose: This paper aimed to investigate the protective mechanism of HPI on asthma and adverse influence on the development of gastric cancer. Method: Information about HPI was obtained from public database Comparative Toxi-cogenomics Database (CTD). The related targets in asthma and gastric carcinoma were attained from the public database Genecards. The ingredients of coptidis rhizoma were obtained from the public database Traditional Chinese Medicine Systems Pharmacology (TCMSP) Network pharmacology including GO enrichment analysis, KEGG enrichment analysis and molecular docking was utilized. Protein-protein internet was constructed to analyse the functional link of target genes. Molecular docking via Autodockvina was employed to study the potential effects on key target genes. Result: The top 10 key targets of HPI for asthma were CXCL9, CX3CL1, CCL20, CCL4, PF4, CCL27, C5AR1, PPBP, KNG1 and ADORA1. The GO biological process involved mainly included leukocyte migration, response to bacterium. The (R)-canadine and quercetin were filtered from coptis chinensis according to network pharmacology theories, which were employed to explore that there was a possibility that they inhibited the HP infection synchronously and protect against asthma. The targets of (R)-Canadine were SLC6A4 and OPRM1. For ingredients quercetin, its targets are AKR1B1 and VCAM1. Conclusion: CXCL9 and VCAM1 were the common targets of asthma and HPI, which might be one imported target of HP infection for asthma. Quercetin could be an effective ingredient to suppression HP infection and help prevent asthma.